Parental Engagement in Early School Readiness. - Cates, Sherra.; Nitzberg, Katie.; Turnquest, Krysti. (Tufts University. Tisch Library., 2018)
2013 M.A. in Urban and Environmental Policy and Planning Field Project. Client: Dudley Street Neighborhood Initiative.